FAITH IN THE HUMAN EDUCATION - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2008)
In the secular society the youth avoids religion and its lessons at school. It provides conditions for weakening moral education, understanding the human worth in this world. All religion lessons support religious education in different branches of science at school and the community. The branches of andragogy such as pedagogy, andragogy, gerontagogy research human education in all levels of human ages and prepare methods for the interaction of estethical, moral and religious human development. In Lithuania there are good conditions for human education, but active involvement of families and pedagogical institutions is lacking. The statesmen must concern about the activity of educators. To make it possible to restore the youth’s religiosity.
Keywords: faith; religion; religiousnes; age stages; educology